Enhancing speaking skills of beginner level students through the co-teaching method in efl classrooms - Morales Cobeña, Jonathan Omir (2025)
This study evaluated the effectiveness of the co-teaching method for enhancing the oral skills of beginner-level English as a Foreign Language (EFL) students within the Ecuadorian public education system. The research addresses systemic challenges such as overcrowded classrooms and traditional methodologies that limit oral practice. Through a mixed-methods action research design with a quasi-experimental approach, an experimental group that received instruction via co-teaching was compared to a control group that followed a traditional model. Data was collected through oral production pre- and post-tests, classroom observations, and student surveys. The quantitative and qualitative results demonstrated that the experimental group achieved significantly greater improvements in their communicative competence. A notable progression was observed in pronunciation, vocabulary, confidence, and engagement, in addition to a substantial reduction of the "affective filter" compared to the control group. Students perceived the co-teaching classes as more dynamic, interactive, and secure. It is concluded that the co-teaching method is an effective and viable pedagogical intervention to foster the development of oral skills in educational contexts with limited resources.